Measuring the impact of an administrative fine on a company and its future survival: A case study from the Czech Republic - Tomas Krabec; Romana Čižinská (Financial Internet Quarterly, 2021)
An administrative fine is a monetary penalty that may be imposed by a supervisory authoritity as an administrative punishment. Such a fine adversely interferes in the cash flow generation of the company in question. The fine can be described as an investment carrying opportunity costs with no economic returns. However, according to the judgment of the Constitutional Court of the Czech Republic Pl. ÚS 3/02 of 13 August 2002 it is submitted that the fine cannot be imposed in such an amount that would ultimately be liquidating for the sanctioned entrepreneur. The as- sessment of whether the specific amount of the fine imposed represents such an intensive inter- ference with the entrepreneur's property that his business activity becomes pointless (i.e., in the long run only for the payment of a fine) is elaborated in this article. Based on a case study from the Czech Republic, this article deals with an example of a suitable methodological procedure, on the basis of which it is possible to evaluate the impact of a specific amount of fine imposed on the property of a sanctioned entrepreneur and assess ex ante whether (i) continuity of his busi- ness will be interrupted in the future, i.e., when, as a result of the payment of the fine, he even- tually goes bankrupt in the form of insolvency or over-indebtedness and / or (ii) his business ac- tivity will only serve to pay the fine and thus become "pointless". The presented economic narra- tive and methodology are relevant for policy makers and, particularly, for supervisory authorities imposing the fines or assessing the requests for remission.
Keywords: G30; 330; fine; administrative punishment; property relations of the entrepreneur; going concern